Balancing excellence: Character development and academic support in special sports classes - Mulyadi, Eko; Ishafit; Widodo, Hendro; Montaño, Elsa Carmen N. (Universitas Ahmad Dahlan, 2025)
This study examines the process of character development and academic services implemented in Special Sports Classes (SSC) at State Senior High School 1 Pengasih. It identifies key character values emphasized in student development, including discipline, teamwork, sportsmanship, responsibility, and perseverance, and explores student motivation, academic support, challenges, interactions, and the achievements and expectations of student athletes, teachers, coaches, and program coordinators. Using a qualitative approach, data were collected through observation, interviews, and documentation involving teachers, trainers, students, and SSC administrators. The findings show that student athletes are motivated to enhance their knowledge and skills in sports, develop personal potential, and benefit from structured support within the SSC program. Their interest in joining SSC varies, beginning from elementary to junior high school levels. Academic services are generally supportive, with flexible schedules and additional assistance provided by subject teachers when students miss lessons due to training or competitions. However, scheduling conflicts between training and academic activities remain a key challenge, although these are often mitigated through adaptive learning support. Interactions among teachers, coaches, and students foster positive communication and emotional support, helping students manage stress through constructive strategies. Student achievements have reached the national level, with aspirations extending to international competitions. Nevertheless, academic services are not yet fully optimized, as they do not sufficiently differentiate SSC students from regular or inclusive programs. Additional challenges include the lack of specialized programs and logistical constraints such as long travel distances. These findings provide practical insights and policy recommendations for improving SSC implementation and supporting athlete-centered education.